Construção de um robô SCARA colaborativo com base em sensoriamento capacitivo de baixo custo - Martos, Lucas Santana (Universidade Federal de São Carlos, 2024)
The robotics trade is predicted to experience exponential growth until 2038. Industrial automation aims to replace manual labor with automated robots, impacting companies of all sizes, especially in the Asian market where there is significant financial investment and available technology. In Brazil, there is an observed increase in automation, although small and medium-sized enterprises face significant challenges. Collaborative robots, also known as cobots, are being introduced to make automation more accessible, although the price of sensors remains a barrier. SCARA robots stand out for their efficiency in planar assembly tasks due to their structure and speed. Cobots are characterized by having sensing capabilities to deal with the presence of individuals in their work environment, either by stopping or by joint action, using optical, contact, radar, and various other sensors. This paper presents the development of a SCARA robotic arm, emphasizing its accessibility and efficiency for small and medium-sized enterprises. The mechanical assembly was optimized to reduce costs and simplify the manufacturing process. The electronic system was implemented using the Arduino UNO microcontroller due to its simplicity and affordable cost, despite being sensitive to noise. Mathematical modeling based on inverse kinematics was crucial for precise control of the robotic arm's position. Tactile sensing was addressed economically, ensuring accuracy and reliability in contact detection, even on metallic structures, although sensitive to noise, which makes the use of cobots viable in the Brazilian market and stimulates the growth of the national industry.
Construction of a collaborative SCARA robot based on low-cost capacitive sensing
Keywords: Braços robóticos; SCARA; Sensoriamento capacitivo; Robôs colaborativos; cobots; ENGENHARIAS::ENGENHARIA MECANICA